Cooperative writing in language-diverse learning groups: Opportunities and didactic perspectives for promoting writing in primary education (Pedagogical Horizons, 2025)
Cooperative writing can promote the linguistic and social skills of learners in heterogeneous primary school learning groups. By exchanging ideas and working on texts together, pupils can improve their writing skills and learn to give and accept constructive feedback. This not only strengthens linguistic expression, but also promotes teamwork and communication among learners. This article highlights both the opportunities offered by cooperative writing – e.g. improving writing skills and promoting reflective thinking – and potential obstacles, such as different performance levels and working styles within groups. In addition, practical tips are provided on how cooperative writing can be effectively implemented in a school context, for example through the targeted planning of group activities, the introduction of structured feedback processes and the promotion of an open communication culture.
Keywords: improving writing skills; heterogeneous learning groups; German didactics